Investigation of the Reference Level Description for Arabic Proficiency Tests in Indonesia - Maulani, Hikmah; Muthmainah, Nur; Khalid, Shofa Musthofa; Saleh, Nalahuddin; Taufik, Ijlal Haziel (Universitas Islam Negeri Raden Intan Lampung, 2024)
This article aimed to map the reference level description of the Arabic Language Proficiency Test in Indonesia with an adaptation based on the Common European Framework of Reference for Languages (CEFR). In this context, the article focused on developing reference level descriptions to assess Arabic language proficiency in Indonesia. A qualitative approach was used through document analysis. Evaluation questions on the Ikhtibarat Maharah Lughah Arabiyah (Imalah) test were cariied out as the data source as well as the CEFR guiding concept issued by Council of Europe. This research was carried out according to the design, namely starting with collecting data in the form of documents related to the CEFR and Arabic language tests, then the data collected was reduced and presented in the form of tables, diagrams or narratives and at the end there were conclusions drawn. The findings of this study reinforced the research objectives by demonstrating that the test includes reference level descriptions that are international standards. This assisted in assessing and understanding the extent to which an individual has mastered the Arabic language. In other words, these findings confirmed that the implementation of international reference level descriptions in the test supports the achievement of the established research objectives, which was to assist in assessing the language proficiency of individuals in Arabic. By adopting the CEFR, this not only helped to measure language proficiency easier, but also facilitated a better understanding of the level of Arabic competency required for educational, employment or general communication purposes.